A Multiwavelength Analysis of the Spiral Arms in the Protoplanetary Disk Around Waoph 6 - Weber, P (EDP Sciences, 2021)
Context. In recent years, protoplanetary disks with spiral structures have been detected in scattered light, millimeter continuum, and CO gas emission. The mechanisms causing these structures are still under debate. A popular scenario to drive the spiral arms is the one of a planet perturbing the material in the disk. However, if the disk is massive, gravitational instability isusually the favored explanation. Multiwavelength studies could be helpful to distinguish between the two scenarios. So far, only a handful of disks with spiral arms have been observed in both scattered light and millimeter continuum. Aims. We aim to perform an in-depth characterization of the protoplanetary disk morphology around WaOph 6 analyzing data obtained at different wavelengths, as well as to investigate the origin of the spiral features in the disk. Methods. We present the first near-infrared polarimetric observations of WaOph 6 obtained with SPHERE at the VLT and compare them to archival millimeter continuum ALMA observations. We traced the spiral features in both data sets and estimated the respective pitch angles. We discuss the different scenarios that can give rise to the spiral arms in WaOph 6. We tested the planetary perturber hypothesis by performing hydrodynamical and radiative transfer simulations to compare them with scattered light and millimeter continuum observations. Results. We confirm that the spiral structure is present in our polarized scattered light H-band observationsof WaOph 6, making it the youngest disk with spiral arms detected at these wavelengths. From the comparison to the millimeter ALMA-DSHARP observations, we confirm that the disk is flared. We explore the possibility of a massive planetary perturber driving the spiral arms by running hydrodynamical and radiative transfer simulations, and we find that a planet of minimum 10 MJup outside of the observed spiral structure is able to drive spiral arms that resemble the ones in the observations. We derive detection limits from our SPHERE observations and get estimates of the planet s contrast from different evolutionary models. Conclusions. Up to now, no spiral arms had been observed in scattered light in disks around K and/or M stars with ages <1 Myr. Future observations of WaOph 6 could allow us to test theoretical predictions for planet evolutionary models, as well as give us more insightinto the mechanisms driving the spiral arms. © 2021 S. B. Brown-Sevilla et al.